Prevalence of calves coccidiosis in Jimma town dairy farms, South-Western Ethiopia - Kabeta Yadeessa, Tadele; Degefu Awash, Hailu; Kebede Gurmu, Girma (Scientific Journal of Zoology, 2014)
A cross- sectional study was conducted from October 2009 to March 2010 on Jimma town dairy farms to determine the prevalence of Calves coccidian and assess associated risk factors. Faecal samples were collected once from a total of 385 calves range from 5-365 days old and examined for the oocysts of Eimeria species by centrifugal faecal flotation technique using concentrated sucrose solution. Out result revealed that overall prevalence of 198(51.42%) Eimeria species. Of the 53 dairies sampled, almost all of the farms had calves shedding Eimeria oocysts. The species of Eimeria circulating in the farms was presumed to be based on morphology of the oocysts and certain epidemiological features of the Eimeria, a total of 8 species were identified namely Eimeria bovis 94(24.4%), Eimeria zuernii 58(15.1%), Eimeria auburnensis 56(14.6%), Eimeria Canadensis 53(13.8%), Eimeria ellipsoidalis 28(7.3%), Eimeria subspherica 22(5.7%), Eimeria cylindrical 20(5.2%) and Eimeria alabamensis 16(4.2%) in descending order of their relative prevalence. Eimeria species were not found to be statistically associated with faecal consistency, breed and sex (P>0.05). Among the risk factors studied, hygiene status and age of the calves were the most important factors associated with the possibility of infection with diseases. The mean and maximum Eimeria oocysts per gram of faeces (OPG) determined by using McMaster technique was 100 and 24,000, respectively. Coccidiosis is a common and important cause of morbidity and economical loss in calves in study areas. Hence appropriate disease prevention and control measure is paramount importance to reduce these impacts.